QUALITATIVE EVALUATION OF ACID SILAGE PREPARED FROM FISH WASTE COLLECTED FROM THE MARKET - Baraiya, Ravi; Pathan, Dabir; Sharangdher, Shrikant; Wasave, Suhas; Rathod, Sanjaykumar Karsanbhai; Mohite, Ashish (Journal of the Inland Fisheries Society of India, 2023)
The aim of this research was to use three distinct acids to convert fish market waste into protein-rich silage: formic acid (3.5%), lactic acid (2.5, 3.5, 4.5 and 5.5%) and acetic acid (2.5, 3.5, 4.5 and 5.5%). Raw papaya (Carica papaya) was used as a catalyst to accelerate the process of fermentation. The proximate composition of the fish waste was moisture (79.34 ± 0.27%), crude protein (15.53 ± 0.09%), fat (2.72 ± 0.06%) and ash (2.40 ± 0.15%). The nutritional, biochemical and microbiological properties of various acid-preserved fish silage were analyzed at ambient temperature during a study period of 60 days. Treatments A1 (2.5% lactic acid), A2 (3.5% lactic acid) and B1 (2.5% acetic acid) were spoiled at the end of the 12th, 18th and 12th days, respectively. The pH, TMA and TVB-N values were increased with duration and then stable up to 60 days. The TPC count showed a decreasing trend and was not detected after six days. The protein content of acid silages after 60 days, treatment FA (3.5% formic acid), A4 (4.5% lactic acid), B2 (3.5% acetic acid) and B3 (4.5% acetic acid) had greater values of 13.81 ± 0.07, 13.10 ± 0.02, 13.56 ± 0.03 and 13.79 ± 0.07%, respectively. The treatments FA (3.5% formic acid), A4 (5.5% lactic acid) and B3 (4.5% acetic acid) gave almost similar results. The present study revealed that lactic acid and acetic acid could substitute formic acid. Acetic acid can substitute formic acid and make it more economically feasible. Fish silage can be stored for up to 60 days without deterioration.